Conjecturas em teorias dos números e suas histórias - Souza, Jucélio de Barros (2019)
In a historical approach, some interesting and intriguing conjectures in number Theory will be studied in this work. The Goldbach's conjecture, one of the most famous in mathematics, for never having been proved, although many ancient and contemporary mathematicians have already made a great deal of effort to find a solution to this problem. Other conjectures mentioned as Collatz, of the Twin Primes,Primes in Arithmetic Progression, as well as the Perfect Numbers and the Mersenne Primes, besides the 196 conjecture, emphasizing the palindromes and the search for the existence of a Lychrel number, are also anxieties that move the field of mathematics , from previous times to the current modern of super computers. But, they are mathematical puzzles that have never been proved, but awaken curiosities in mathematicians and enthusiasts of related areas.